Will the Emergence of the Euro Affect World Commodity Prices? - Liang, Hong (IMF Working Papers; Working Paper ;, 2000)
This study provides evidence that episodes of internal stability of exchange rates among the 11 Euro countries during 1957-98 were associated with periods of lower real commodity price volatility. These stabilizing effects are statistically significant for fertilizer, metals, petroleum, and cereals. A reasonable inference, therefore, is that the establishment of the Euro on January 1, 1999, should be expected to contribute to reduced volatility of world commodity prices, other things equal, although the impacts are likely to be modest.